Clinico-hematological Study of Theileriosis in Gir and Jaffrabadi Calves - Brahmbhatt, NN; Kumar, B; Thakre, BJ; Parmar, VL; Choravada, DR; Patel, JA (Indian Journal of Veterinary Sciences and Biotechnology, 2019)
The present study was undertaken to know the hematological alteration in Theileria infected Gir and Jaffrabadi calves in and around Junagadh, Gujarat. Young calves (less than one year of age) with suspected clinical signs of hemoprotozoan infection, presented at the Veterinary Clinical Complex of the College in Junagadh, were taken in this study. Out of 64 suspected cases examined, 13 (20.31%) were found positive for Theileria infection by microscopic blood smear examination. The prevalence of Theileria infection was more in the rainy season (27.27%) followed by summer (26.31%) and least in the winter season (8.69%). Theileria infection was significantly (p <0.05) higher in young calves of less than 6 months of age (31.0 %) as compared to calves of 6–12 months of age (9.1%). A nonsignificant higher infection was recorded in Gir calves (22.22%) than Jaffrabadi calves (17.85%). There was no effect of breed, sex or season on Theileria infection in Gir and Jaffrabadi calves in and around Junagadh. Hematological studies revealed anemic condition and increased total leukocyte count with neutrophilia and lymphocytopenia.